Factores condicionantes y su influencia en el incumplimiento del esquema de vacuna HPV en niñas de 9 a 10 años en la Unidad Operativa Guasmo Sur – Guayas, Guayaquil diciembre 2022 - mayo 2023. - Carpio Toaza, Juana Piedad (2023)
The purpose of the research is to identify the conditioning factors that influence non-compliance with the HPV vaccine scheme in girls aged 9 to 10 years. A descriptive, explanatory, cross-sectional and quantitative study was carried out, with the support of observation techniques, the surveys are applied to the mothers of the family. The problem lies in non-compliance with the HPV vaccination scheme, due to social and economic factors, the breaking of family ties, ignorance, the high rates of crime and violence in the Guasmo Sur sector -Guayas, Guayaquil, being the parents of family and staff of the Guasmo Sur health center who play the most important role in complying with the established HPV vaccine coverage. As a result of the surveys, we found the main factors such as ignorance and economy and other secondary factors for which children have only one dose of the HPV vaccine. Nursing staff are recommended to constantly work to promote information regarding the Expanded Program on Immunization (EPI). The Pan American Health Organization indicates that the Human Papilloma Virus is responsible for cervical cancer, it also indicates that this disease can be prevented with the application of the vaccine against the human papilloma virus that has been available in Ecuador since 2014 and It is more effective when administered to girls from 9 to 14 years of age.